The Use of Antipsychotic Drugs for Treating Behavioral Symptoms in Alzheimer’s Disease - Calsolaro, Valeria; Antognoli, Rachele; Okoye, Chukwuma; Monzani, Fabio (Frontiers in Pharmacology, 2019)
According to the World Alzheimer’s report, dementia was estimated to affect 50 million worldwide in 2018, number expected to increase to more than 150 million within 30 years. Alzheimer’s disease is the most common type of dementia, accounting on its own for 2/3 of all dementia cases. The initial signs and symptoms of Alzheimer’s disease relate to progressive cognitive decline, inexorably progressing until the loss of independence. Neuropsychiatric and behavioural symptoms may occur during the progression of the disease; around twenty percent of patients without any behavioural symptoms at the diagnosis will experience some within 2 years. Consequences are early institutionalization, lower quality of life of both patients and carers, more severe cognitive impairment. Treatment options for behavioural symptoms include pharmacological and non-pharmacological approaches. The latter are usually preferred, since the antipsychotic therapy is not free from several, and often serious, adverse events. However, behavioural symptoms are not always controllable with non-pharmacological intervention. The psychotropic class of medication more frequently prescribed for behavioural symptoms are atypical antipsychotics; among them, risperidone is the only one licensed for the treatment of aggression, in Europe but not in the USA. On that regard, the use of antipsychotic drugs should be limited, due to the increased risk of mortality, stroke, hallucination and higher risk of relapse after discontinuation. Some new agents are under evaluation, such as pimavanserin and lumateperone. In this review, we are evaluating the current available pharmacological options to treat behavioural symptoms, as well as the new agents available.